Predictors of Employability of the Bachelor of Secondary Education Major in Mathematics Graduates - Alcher J Arpilleda; Anthony Mark Joseph M Manile; Pacita I Soringa (Southeast Asian Mathematics Education Journal, 2021)
The goal of every program provided by a school or university is to make it more responsive to the needs of fast-changing employment demands. This goal also entails enhancing the students' skills to be prepared for their future jobs. This study identified the predictors of employability of the Bachelor of Secondary Education Major in Mathematics graduates of St. Paul University Surigao Academic Year 2005-2015. Descriptive survey research was employed using a researcher-made questionnaire encompassing the personal information, employment status, and exit skills with seven identified subparts. The questionnaire elicited employability through the skills of 81.82% of the participants. Utilizing the employment status variables and the exit skills, Linear Regression Analysis extracted the predictors of employability. The findings revealed that the exit skills of the graduates are the predictors of employability. Thus, the school should create programs and activities which enhance the students' skills, particularly the predictors of employability identified in this study.